Transnational Education: The Politics Of Mobility, Migration And The Well-being Of International Students - Kell , Peter; Vogl, Gillian (Penerbit Universiti Sains Malaysia (USM Press), 2008)
This paper explores some of the background issues regarding international students and seeks to identify the ways in which the experience of transnational education by international students in higher education is positioned within academic debates, policy debates, literature and theory. This paper argues about the need for new ways of exploring the phenomena of international education and that many of the theoretical frameworks used are inadequate to account for the complexities that characterise transnational higher education and what international students experienced. In the context of globalisation and anxiety about immigration, the paper argues that the theoretical positions have identified international students as a "risk" but it is more often the student that experiences risk. It is argued that the approaches to researching international students tend to be instrumental and focused on market analysis rather than the experience of students in terms of educational, social and cultural interactions. International students are often constructed as "a problem" and this paper argues for a different approach that sees students as important as "designer migrants' in developed countries, important for capacity building and establishing international networks for their countries of origin. The paper asserts that international students and transnational education should not be seen exclusively in market terms but as an opportunity to develop notions of the "global citizen".